Dravet syndrome in a 3-year-old pediatric patient: case report - K., Shailaja; L., Nissi; A., Tamil Arasi (International Journal Of Community Medicine And Public Health, 2022)
Dravet syndrome (DS) is a severe form of epilepsy that occurs during the first year of life. This is caused by mutations in the voltage-gated sodium channel and characterized by frequent, prolonged seizures often triggered by high body temperature (hyperthermia), developmental delay, ataxia, hypotonia, sleep disturbances which is treated by multiple antiepileptic drugs. In this case report, we will discuss a 3 years old male pediatric patient who presented with complaints of vomiting and lethargies followed by seizures and has been diagnosed with DS since the age of 6 months. He was given with multiple antiepileptic drugs and other drugs for his symptomatic management which resulted in a major drug interaction. From this case report, we will get a clear picture necessitating continuous monitoring in case of polypharmacy.